Polimorfismo no Gene GH, crescimento muscular, expressão de mRNA GHR, IGF-I e HSP70 associados a características de produção em Tilápia do Nilo - Tanamati, Fernanda (2014)
The body growth is one of the most important characteristics in the production of fish. It is a complex response involving nutritional, environmental, genetic and endocrine factors. Thus, two experiments were conducted in which the aim of the experiment I was to check in crossed tilapia GIFT x Thai if the polymorphism in the growth hormone (GH) is associated with performance characteristics and gene expression of the growth hormone receptor (GHR) and insulin-like growth factor - I (IGF-I), and also to check if the size of the fish can alter the expression of heat shock protein HSP70. The aim of the experiment II was to evaluate in crossed tilápia GIFT x Thai, the effect of fasting on the expression level of GHR and IGF-I and to examine whether it changes the performance characteristics and muscle growth. In experiment I, the animals were distributed in a completely randomized design in a factorial arrangement, two genotypes: GH single band (GHbs) and GH dual band (GHbd), and two weight categories: 20-35g and 40-70g. Performance characteristics were evaluated: body weight, empty weight, weight of viscera, fillet weight, length, width, fillet yield and fillet/empty carcass ratio. Fragments of caudal fin were collected for genotyping and liver and white muscle samples were collected for analysis of gene expression. It was observed that the characteristics body weight, empty weight, weight of viscera, fillet weight and length showed higher for genotype GHbd; smaller animals, weight category 20-35g, showed higher expression of HSP70 mRNA expression and no relation between GHR mRNA and IGF-I and GHbs and GHbd was observed. Thus, the change of GH may be associated with performance characteristics and the expression of the HSP70 gene may be influenced by the size of the fish. In the experiment II, fish were subjected to a fasting period of 15 days and they were evaluated on days 0 (C0), 5 (C5 and F5), 10 (C10 and F10) and 15 (C15 and F15). C0, C5, C10 and C15: animals that continued to receive food. J5, J10 and J15: fasted animals. The following measurements were obtained: body weight, empty carcass weight, length and width. Samples of liver and white muscle were collected for analysis of mRNA expression of GHR and IGF-I, and white muscle samples were collected for assessment of muscle growth with determining the smallest diameter grouped into different classes. Feed restriction reduced the average of all performance traits, and analyzing fasted tilapia and tilapia that continued receiving food, it was observed that fasting caused increased expression of the GHR hepatic at days 5 and 10, it decreased expression of IGF-I hepatic and increased expression of GHR and IGF -I in white muscle at days 5, 10 and 15. There wasn?t modification of muscle growth when fasted animals were compared with animals that were fed. Thus, the expression of GHR and IGF-I genes in the liver and in white muscle, as well as in the performance, were influenced by fasting.